Plantation Under Compensatory Afforestation Fund Management and Planning Authority Transforming Jhum Cultivation to a Diverse Agroforestry System: Introspection from Phalong Village, Manipur - Giri, Krishna; Das, Niren; Bora, Navajyoti (Indian Forester, 2020)
CAMPA is a National Advisory Council for monitoring, technical assistance and evaluation of compensatory afforestation activities in entire nation. Monitoring and evaluation work of Tamenglong Forest Division, Manipur was carried out in 2018. The field observations from Phalong Village, Manipur revealed that additional compensatory afforestation undertaken in jhum paddy fields was excellently maintained by the farmer. The farm agro biodiversity of this plantation site was very high, which seems to be transforming rice monoculture in to a diverse agroforetry system. This article aims to highlight the innovations of farmer in transforming jhum paddy monoculture to a diverse agroforestry model through plantation done under the scheme of CAMPA.